Efektivitas Penggunaan Flipbook sebagai Media Pembelajaran Interaktif di SMA/SMK: Tinjauan Literatur - Enni Setyorini; Sukarmin Sukarmin; Harlita Harlita (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
In an increasingly advanced digital era, the utilization of technology in education is a must to improve the qualityof learning. One of the innovations that are starting to be widely applied is the use of interactive learning media,such as flipbooks. Flipbook is a digital media that presents learning materials in the form of interactive booksequipped with various features, such as animation, audio, and video. This allows students to learn more dynamicallyand fun, so it is expected to increase their interest and understanding of the material presented. This literature studyaims to review various literatures that discuss the effectiveness of using flipbooks as interactive learning media inSMA/SMK. This article uses a literature review research method with reference sources derived from previousresearch journals. The results of the journal search were 7 journals that met the inclusion criteria determined by theresearcher. The research found most used ADDIE. There were different results in each study, but still showedsimilarities, namely an increase in learning in each study. Based on the literature review that has been conducted, itcan be concluded that the use of flipbooks as interactive learning media in SMA / SMK has significant potential inincreasing the effectiveness of learning. Flipbooks offer various advantages, such as a more interesting presentationof material, high interactivity, and the ability to integrate various multimedia elements. This allows students to moreeasily understand the concepts taught, as well as increase their motivation and involvement in the learning process